Global Standards, Local Voices: Mapping Latin American Participation in the IETF Meetings - Silva, Priscylla; Silva, Pedro; Braga, Julião; Santos, Marcelo (Anais do Workshop Pré-IETF (WPIETF), 2025)
The Internet Engineering Task Force (IETF) is one of the main global organizations developing and maintaining the technical standards that sustain the Internet. Although open and volunteer-based, participation remains geographically concentrated. This paper examines the dynamics of Latin American and Caribbean participation, identifying who contributes, from which institutions and sectors, and what factors shape engagement. We created a longitudinal dataset covering all IETF meetings (IETF 1-123), consolidating information on participants’ names, affiliations, countries, and registration types. The analysis shows that North America and Europe dominate participation, while Latin America and the Caribbean, led by Brazil, show gradual growth since the 2010s. Regional engagement centers on NIC.br, LACNIC, and universities, supported by fellowships and remote participation hubs.